Will the Covid-19 Pandemic Leave a Lasting Legacy in Children's Skill Development? - Katharina Werner; Ludger Woessmann (CESifo Forum, 2021)
For school children, the Covid-19 pandemic brought school closures that challenged their learning experiences and social-distancing rules that impeded their peer interactions. Will these experiences have persistent effects on the development of children's cognitive and socio-emotional skills? We summarize the available evidence on how the pandemic affected the educational inputs provided by children, parents, and schools, how it impacted children's cognitive and socio-emotional development, and what this means for later economic outcomes. There is clear evidence that the Covid-19 pandemic seriously impeded the cognitive and socio-emotional development of many children. If remediation fails, these skill losses are likely to reduce skill development, lifetime income, and economic growth and increase educational and economic inequality in the long run.
Keywords: 330